TOEFL untuk Meningkatkan Kualitas Bahasa Inggris Peserta Didik: Pelatihan dan Praktik - Nita Sutanti; Salma Salma (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
TOEFL or known as the Test of English as a Foreign Language is an English test that is used to measure the level of mastery of a student's English through listening, reading, and writing and structural expressions. This test is very useful for high school students. One of the benefits that can be felt by students is as preparation for college level. With good English skills, it will produce a maximum TOEFL score. Community service activities that have been carried out for JAYABAYA Tutoring students using the lecture, discussion, and practice methods of working on TOEFL questions. The lecture method used to motivate as well as deliver the material makes students feel enthusiastic about trying to work on the TOEFL questions. The method of discussion and practice is carried out to determine the level of students' English mastery through the TOEFL test. By providing discussions and opportunities to do TOEFL Exercises, it increases students' motivation to learn English